Políticas públicas para o ensino superior brasileiro 2003-2014, uma análise do Prouni e Fies - Moura, Tatyane (2016)
The present dissertation has as its general objective to talk about the public education policies, in Partido dos Trabalhadores government (2003-2014). Specifically analyzing Programa Universidade Para Todos (ProUni) and Fundo de Financiamento ao Estudante do Ensino Superior (FIES), which are access policies to higher education, focused on Private Education Institutions. The methodology chosen for the study was the documentary one, which was divided into bibliographic research and legislation research. The main question from this research brings to public policies of access to higher education in Brazil, from 2003 to 2004, specifically ProUni and FIES. To answer this question, this work was divided in 4 chapters: the first chapter brings the introduction to the subject developed in this research, the second one brings notes about higher education history in Brazil; the third one discusses about the public education policies for higher education from 2003 until 2014, and the last one treats specifically about ProUni and FIES. Along this dissertation, it will be shown how the government of that period did not break the neoliberal policies of its previous government and how those policies were beneficial to private initiative. The conclusion shows that, despite all these, a lot was done about the higher education in the period analyzed. However, it’s an on-going process of reaching the claim of society. There is still a long way to be covered to really reach a higher education that is inclusive, fair, of quality and committed to the country development. To actually consolidate the democracy policies, its needed to be think not only in the expansion and the access in higher education, but the less privileged student permanency at the higher education.